Preparation method of sulfentrazone and catalyst

By modifying the magnetic iron tetroxide, Cu, Co and La element composite catalyst on the pleated graphene oxide sheet support, the reaction is heated and refluxed to produce mesylamide, which solves the problems of high raw material consumption and environmental pollution, and realizes the Efficient and environmentally friendly synthesis of mesylamide, and the catalyst is easy to be separated and reused.

CN119306676APending Publication Date: 2025-01-14HUNAN SPARK SCI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411408357.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-19
Filing Date
2024-10-10
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing methylsulfonamide synthesis methods have high raw material consumption, severe environmental pollution, difficult catalyst recovery and poor stability, which affects industrial application.

Method used

Using a modified pleated graphene oxide sheet support, a composite catalyst of magnetic iron tetroxide, Cu, Co and La elements was deposited, and agitated reaction was heated and refluxed to obtain mesylamide, avoiding high temperature and high pressure conditions, and realizing the catalyst. Easy to separate and reuse.

Benefits of technology

It improves the conversion rate of raw materials and product yield, reduces side reactions, has high product purity, stable catalysts, avoids environmental pollution, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005077299360000011
    Figure BDA0005077299360000011
  • Figure BDA0005077299360000012
    Figure BDA0005077299360000012
  • Figure BDA0005077299360000021
    Figure BDA0005077299360000021
Patent Text Reader

Abstract

The invention provides a preparation method of sulfentrazone and a catalyst, and belongs to the technical field of organic chemistry. The intermediate and methylsulfonyl chloride are subjected to a heating reflux stirring reaction under the action of a catalyst, and sulfentrazone is prepared; the catalyst is a compound formed by depositing magnetic ferroferric oxide and Cu and Co elements after the surface of a wrinkled graphene oxide sheet is modified by tannic acid and doping La elements. The method for preparing sulfentrazone is simple, avoids harsh conditions of high temperature and high pressure, is safe and environment-friendly, avoids environmental pollution, and the catalyst is easy to separate, reusable, high in catalytic activity, high in reaction raw material conversion rate, high in product yield, few in side reaction, high in product purity and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic chemistry, and in particular to a preparation method and a catalyst of sulfentrazone. Background Art

[0002] Sulfonamide is a herbicide belonging to the triazolinone class, with the chemical name N-(2,4-dichloro-5-(4-difluoromethyl-4,5-dihydro-3-methyl-5-oxo-1H-1,2,4-triazol-1-yl)phenyl)methanesulfonamide (structural formula is shown in Formula I).

[0003]

[0004] At present, the synthesis of sulfentrazone requires two steps. First, 2-(5-amino-2,4-dichlorophenyl)-3-methyl-4-difluoromethyl-2,4-dihydro-5methyl-3hydro-1,2,4-triazolin-3-one (hereinafter referred to as compound II) and methylsulfonyl chloride react in dichloromethane solvent under the action of triethylamine, an acid-binding agent, to generate a bismethylsulfonylamine derivative (compound III); compound III is then hydrolyzed with sodium hydroxide aqueous solution in an ethanol solution to obtain sulfentrazone with a yield of 66%. In the reaction, 2.25 mol of methylsulfonyl chloride and 2.25 mol of triethylamine are consumed for each molecule of compound II. The consumption of raw material methylsulfonyl chloride is high, and a large amount of triethylamine hydrochloride needs to be neutralized with alkali and recovered into triethylamine for reuse, and the recovery rate of triethylamine is low. In addition, the sodium methylsulfonate generated by the hydrolysis reaction of compound II with sodium hydroxide solution is easy to pollute the environment.

[0005]

[0006]

[0007] Therefore, there is an urgent need to find an efficient and environmentally friendly method for synthesizing sulfentrazone. Summary of the invention

[0008] The purpose of the present invention is to provide a preparation method and catalyst of sulfentrazone. The method is simple, avoids the harsh conditions of high temperature and high pressure, is safe and environmentally friendly, and avoids causing environmental pollution. The catalyst of the present invention is easy to separate and can be reused, has high catalytic activity, high reaction raw material conversion rate, high product yield, few side reactions, high product purity, and has broad application prospects.

[0009] The technical solution of the present invention is achieved in this way:

[0010] The present invention provides a method for preparing sulfentrazone, wherein an intermediate and methylsulfonyl chloride are subjected to a heating reflux stirring reaction under the action of a catalyst to prepare sulfentrazone; the catalyst is a composite material in which magnetic ferrosoferric oxide and Cu and Co elements are deposited on the surface of a wrinkled graphene oxide sheet after being modified with tannic acid, and the composite material is doped with La element:

[0011] The structural formula of the intermediate is shown in Formula II:

[0012]

[0013] As a further improvement of the present invention, the molar ratio of the intermediate to methanesulfonyl chloride is 1:1.05-1.1.

[0014] As a further improvement of the present invention, the added amount of the catalyst is 0.5-1 wt % of the total mass of the reactants.

[0015] As a further improvement of the present invention, the preparation method of the catalyst is as follows:

[0016] S1. Preparation of wrinkled graphene oxide sheets: spray drying a graphene oxide aqueous dispersion, and ball milling to obtain wrinkled graphene oxide sheets;

[0017] S2. Preparation of tannic acid modified wrinkled sheet: adding the wrinkled graphene oxide sheet obtained in step S1 to water, adding tannic acid and a catalyst, heating and stirring to react, centrifuging, washing, and drying to obtain a tannic acid modified wrinkled sheet;

[0018] S3. Preparation of magnetically modified corrugated sheet: adding the tannic acid modified corrugated sheet obtained in step S2 to water, adding ferric chloride and ferrous chloride, adding ammonia water dropwise under inert gas protection, heating and stirring the reaction, separating with a magnet, washing, and drying to obtain a magnetically modified corrugated sheet;

[0019] S4. Copper / cobalt deposition: dissolving a copper salt and a cobalt salt in water, adding the magnetically modified corrugated sheet and the complexing agent obtained in step S3, evaporating the solvent, washing, drying, and ball milling to obtain a Cu / Co deposited magnetically modified corrugated sheet;

[0020] S5. Lanthanum doping: dissolve lanthanum salt in water, add the Cu / Co deposited magnetic modified wrinkled sheet obtained in step S4, evaporate the solvent, wash, dry, and obtain a catalyst.

[0021] As a further improvement of the present invention, the concentration of the graphene oxide aqueous dispersion in step S1 is 0.5-1 mg / mL, the spray drying conditions are as follows: the inlet air temperature is 80-100°C, the outlet air temperature is 30-50°C, the evaporated water volume is 1700-2200 mL / h, and the ball milling time is 1-2h.

[0022] As a further improvement of the present invention, the mass ratio of the wrinkled graphene oxide sheet, tannic acid and catalyst in step S2 is 10:1-2:0.2-0.3, the catalyst is a Tris-HCl solution with a pH of 9-9.5, the temperature of the heating and stirring reaction is 40-50°C, and the time is 2-4h.

[0023] As a further improvement of the present invention, the mass ratio of the tannic acid modified pleated sheet, ferric chloride, ferrous chloride and ammonia water in step S3 is 10-15:3.2-3.3:1.2-1.3:4-6, and the temperature of the heating and stirring reaction is 70-80°C and the time is 3-5h.

[0024] As a further improvement of the present invention, the copper salt in step S4 is selected from at least one of copper chloride, copper acetate, copper sulfate, and copper nitrate, the cobalt salt is cobalt chloride, the complexing agent is at least one of EDTA, disodium EDTA, ethylenediamine, and triethylamine, the mass ratio of the copper salt, the cobalt salt, the magnetically modified corrugated sheet, and the complexing agent is 5-6:1-2:10-12:7-10, and the ball milling time is 1-2h.

[0025] As a further improvement of the present invention, the lanthanum salt in step S5 is lanthanum chloride, and the mass ratio of the lanthanum salt to the Cu / Co deposited magnetic modified corrugated sheet is 0.5-1:50.

[0026] The present invention further provides a catalyst, the preparation method of which comprises the following steps:

[0027] S1. Preparation of wrinkled graphene oxide sheets: spray-drying a 0.5-1 mg / mL aqueous dispersion of graphene oxide, and ball-milling for 1-2 h to obtain wrinkled graphene oxide sheets;

[0028] The spray drying conditions are as follows: the air inlet temperature is 80-100°C, the air outlet temperature is 30-50°C, and the evaporated water volume is 1700-2200mL / h;

[0029] S2. Preparation of tannic acid modified wrinkled sheet: 10 parts by weight of the wrinkled graphene oxide sheet obtained in step S1 is added to water, 1-2 parts by weight of tannic acid and 0.2-0.3 parts by weight of catalyst are added, heated to 40-50°C, stirred for reaction for 2-4h, centrifuged, washed, and dried to obtain a tannic acid modified wrinkled sheet;

[0030] The catalyst is a Tris-HCl solution with a pH of 9-9.5;

[0031] S3. Preparation of magnetically modified corrugated sheet: 10-15 parts by weight of the tannic acid modified corrugated sheet obtained in step S2 is added to water, 3.2-3.3 parts by weight of ferric chloride and 1.2-1.3 parts by weight of ferrous chloride are added, 4-6 parts by weight of ammonia water are added dropwise under inert gas protection, heated to 70-80 ° C, stirred for 3-5h, separated by magnet, washed, and dried to obtain a magnetically modified corrugated sheet;

[0032] S4 copper / cobalt deposition: 5-6 parts by weight of copper salt, 1-2 parts by weight of cobalt salt dissolved in water, adding 10-12 parts by weight of the magnetically modified corrugated sheet obtained in step S3 and 7-10 parts by weight of a complexing agent, evaporating the solvent, washing, drying, ball milling 1-2h, to obtain a Cu / Co deposited magnetically modified corrugated sheet;

[0033] S5. Lanthanum doping: Dissolve 0.5-1 parts by weight of lanthanum chloride in water, add 50 parts by weight of the Cu / Co deposited magnetic modified wrinkled sheet obtained in step S4, evaporate the solvent, wash, and dry to obtain a catalyst.

[0034] The present invention has the following beneficial effects:

[0035] The present invention heats the intermediate and methylsulfonyl chloride under the action of a catalyst to reflux and stir the reaction to obtain sulfentrazone. When tetramethylammonium chloride is used as a catalyst to catalyze the above reaction, the raw material conversion rate can reach 99%, and the content of sulfentrazone can reach 93%. However, tetramethylammonium chloride is a strong alkaline substance, which is not easy to recycle and is easily soluble in water, which increases the burden of wastewater treatment in post-treatment. In addition, tetramethylammonium chloride is easy to absorb moisture, easy to volatilize, and unstable, which increases the difficulty of its storage, and decomposes into harmful gases at high temperatures. Moreover, methylsulfonyl chloride can only ensure a high raw material conversion rate when it is in large excess. Therefore, if a recyclable catalyst with strong stability and good catalytic effect can be developed, the industrial application of the reaction will be greatly improved.

[0036] The catalyst prepared by the invention is not only easy to separate, but also can repeat the catalytic reaction for many times and still maintain a high catalytic activity, and the catalyst is stable and easy to store, and can efficiently catalyze the reaction, and can achieve a high raw material conversion rate when the methylsulfonyl chloride is slightly excessive, with less side reactions and a high product yield.

[0037] The present invention prepares a catalyst, using a wrinkled graphene oxide sheet obtained by spray drying and ball milling as a carrier, the graphene oxide aqueous dispersion passes through a nozzle and is broken into small droplets, and enters a cyclone separator with heated gas, the solvent evaporates quickly, and the volume of the droplets shrinks quickly, thereby obtaining wrinkled graphene microspheres, and after being broken by ball milling, wrinkled graphene oxide sheets are obtained, which can effectively reduce the stacking of graphene oxide and avoid agglomeration caused by the ordered structure between the sheets, and have good dispersibility. At the same time, the wrinkled carrier greatly increases the specific surface area of ​​the carrier, so that it can load more metal catalysts.

[0038] At the same time, the hydroxyl groups on the surface of graphene oxide make it easy to load tannic acid on its surface. The abundant active groups such as hydroxyl and carboxyl on the surface can greatly increase the metal loading capacity by forming complex bonds. The surface is loaded with magnetic ferrosoferric oxide. On the one hand, the prepared catalyst can be separated by a magnet for easy recycling. On the other hand, iron metal includes two valence states (trivalent and divalent), and can also participate in catalytic reactions through a specific valence electron structure, thereby improving catalytic efficiency.

[0039] In addition, the present invention deposits copper and cobalt metals. The rich oxidation states of the two metals can also play a catalytic role through a specific valence electron structure. Moreover, the price is low, and they are a good substitute for precious metal catalysts and have a good synergistic catalytic reaction effect.

[0040] The catalyst of the present invention is also doped and loaded with lanthanum metal. The special outer electron structure of the lanthanide metal can greatly improve the catalytic activity of the composite metal, so that the reaction of the present invention can still be carried out efficiently at room temperature and pressure without the need for high-purity oxygen, with high reaction yield and few side reactions.

[0041] The method for preparing sulfentrazone provided by the invention is simple, avoids harsh conditions of high temperature and high pressure, is safe and environmentally friendly, and avoids causing environmental pollution. The catalyst provided by the invention is easy to separate and can be reused, has high catalytic activity, high reaction raw material conversion rate, high product yield, few side reactions, and high product purity, and has broad application prospects. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Graphene oxide aqueous dispersion, 0.5 mg / mL, 1 mg / mL, were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0044] The intermediate was prepared by the method described in the literature: Zhang Yuanyuan, Sun Yonghui, Shi Yueping, et al. Synthesis of the herbicide sulfentrazone [J]. Pesticides, 2013, 52(4): 260-262. The DOI of the literature is: 10.16820 / j.cnki.1006-0413.2013.04.010.

[0045] Preparation Example 1

[0046] A method for preparing a catalyst comprises the following steps:

[0047] S1. Preparation of wrinkled graphene oxide sheets: 0.5 mg / mL of graphene oxide aqueous dispersion was spray dried and ball milled for 1 h to obtain wrinkled graphene oxide sheets;

[0048] The spray drying conditions are as follows: the air inlet temperature is 80°C, the air outlet temperature is 30°C, and the evaporated water volume is 1700 mL / h;

[0049] S2. Preparation of tannic acid modified wrinkled sheet: 10 g of the wrinkled graphene oxide sheet obtained in step S1 was added to 150 mL of water, 1 g of tannic acid and 0.2 g of catalyst were added, heated to 40 ° C, stirred for 2 h, centrifuged, washed, and dried to obtain a tannic acid modified wrinkled sheet;

[0050] The catalyst is a Tris-HCl solution with a pH of 9;

[0051] S3. Preparation of magnetically modified pleated sheet: 10 g of the tannic acid-modified pleated sheet obtained in step S2 was added to 100 mL of water, 3.2 g of ferric chloride and 1.2 g of ferrous chloride were added, 4 g of ammonia was added dropwise under nitrogen protection, heated to 70 ° C, stirred for 3 h, separated by magnet, washed, and dried to obtain a magnetically modified pleated sheet;

[0052] S4. Copper / cobalt deposition: 5 g of copper nitrate and 1 g of cobalt chloride were dissolved in 100 mL of water, 10 g of the magnetically modified wrinkled sheet obtained in step S3 and 7 g of EDTA were added, the solvent was evaporated, washed, dried, and ball-milled for 1 h to obtain a Cu / Co deposited magnetically modified wrinkled sheet;

[0053] S5. Lanthanum doping: Dissolve 0.5 g of lanthanum chloride in 100 mL of water, add 50 g of the Cu / Co deposited magnetic modified wrinkled sheet obtained in step S4, evaporate the solvent, wash, and dry to obtain a catalyst.

[0054] Preparation Example 2

[0055] A method for preparing a catalyst comprises the following steps:

[0056] S1. Preparation of wrinkled graphene oxide sheets: 1 mg / mL of graphene oxide aqueous dispersion was spray dried and ball milled for 2 h to obtain wrinkled graphene oxide sheets;

[0057] The spray drying conditions are as follows: the air inlet temperature is 100°C, the air outlet temperature is 50°C, and the evaporated water volume is 2200 mL / h;

[0058] S2. Preparation of tannic acid modified wrinkled sheet: 10 g of the wrinkled graphene oxide sheet obtained in step S1 was added to 150 mL of water, 2 g of tannic acid and 0.3 g of catalyst were added, heated to 50 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain a tannic acid modified wrinkled sheet;

[0059] The catalyst is a Tris-HCl solution with a pH of 9.5;

[0060] S3. Preparation of magnetically modified pleated sheet: 15 g of the tannic acid-modified pleated sheet obtained in step S2 was added to 100 mL of water, 3.3 g of ferric chloride and 1.3 g of ferrous chloride were added, 6 g of ammonia was added dropwise under nitrogen protection, heated to 80 ° C, stirred for 5 h, separated by magnet, washed, and dried to obtain a magnetically modified pleated sheet;

[0061] S4. Copper / cobalt deposition: 6 g of copper sulfate and 2 g of cobalt chloride were dissolved in 100 mL of water, 12 g of the magnetically modified corrugated sheet obtained in step S3 and 10 g of ethylenediamine were added, the solvent was evaporated, washed, dried, and ball-milled for 2 h to obtain a Cu / Co deposited magnetically modified corrugated sheet;

[0062] S5. Lanthanum doping: Dissolve 1 g of lanthanum chloride in 100 mL of water, add 50 g of the Cu / Co deposited magnetic modified wrinkled sheet obtained in step S4, evaporate the solvent, wash, and dry to obtain a catalyst.

[0063] Preparation Example 3

[0064] A method for preparing a catalyst comprises the following steps:

[0065] S1. Preparation of wrinkled graphene oxide sheets: 1 mg / mL of graphene oxide aqueous dispersion was spray dried and ball milled for 1.5 h to obtain wrinkled graphene oxide sheets;

[0066] The spray drying conditions are as follows: the air inlet temperature is 90°C, the air outlet temperature is 40°C, and the evaporated water volume is 2000mL / h;

[0067] S2. Preparation of tannic acid modified wrinkled sheet: 10 g of the wrinkled graphene oxide sheet obtained in step S1 was added to 150 mL of water, 1.5 g of tannic acid and 0.25 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain a tannic acid modified wrinkled sheet;

[0068] The catalyst is a Tris-HCl solution with a pH of 9.3;

[0069] S3. Preparation of magnetically modified pleated sheet: 12 g of the tannic acid-modified pleated sheet obtained in step S2 was added to 100 mL of water, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, 5 g of ammonia was added dropwise under nitrogen protection, heated to 75 ° C, stirred for 4 h, separated by magnet, washed, and dried to obtain a magnetically modified pleated sheet;

[0070] S4 copper / cobalt deposition: 5.5g copper chloride, 1.5g cobalt chloride was dissolved in 100mL water, 11g of the magnetically modified corrugated sheet obtained in step S3 and 8g disodium EDTA were added, the solvent was evaporated, washed, dried, and ball milled for 1.5h to obtain Cu / Co deposited magnetically modified corrugated sheet;

[0071] S5. Lanthanum doping: Dissolve 0.7 g of lanthanum chloride in 100 mL of water, add 50 g of the Cu / Co deposited magnetic modified wrinkled sheet obtained in step S4, evaporate the solvent, wash, and dry to obtain a catalyst.

[0072] Comparative Preparation Example 1

[0073] Compared with Preparation Example 3, the difference is that room temperature drying is used instead of spray drying in step S1.

[0074] The details are as follows:

[0075] S1. Preparation of graphene oxide sheets: 1 mg / mL of graphene oxide aqueous dispersion was dried at room temperature and ball-milled for 1.5 h to obtain graphene oxide sheets.

[0076] S2. Preparation of tannic acid modified wrinkled sheet: 10 g of the graphene oxide sheet obtained in step S1 was added to 150 mL of water, 1.5 g of tannic acid and 0.25 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain a tannic acid modified sheet;

[0077] The catalyst is a Tris-HCl solution with a pH of 9.3;

[0078] S3. Preparation of magnetically modified wrinkled sheet: 12 g of the tannic acid modified sheet obtained in step S2 was added to 100 mL of water, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, 5 g of ammonia was added dropwise under nitrogen protection, heated to 75 ° C, stirred for 4 h, separated by magnet, washed, and dried to obtain a magnetically modified sheet;

[0079] S4 copper / cobalt deposition: 5.5g copper chloride, 1.5g cobalt chloride was dissolved in 100mL water, 11g of the magnetic modified sheet obtained in step S3 and 8g disodium EDTA were added, the solvent was evaporated, washed, dried, and ball milled for 1.5h to obtain a Cu / Co deposited magnetic modified sheet;

[0080] S5. Lanthanum doping: 0.7 g of lanthanum chloride was dissolved in 100 mL of water, 50 g of the Cu / Co deposited magnetic modified sheet obtained in step S4 was added, the solvent was evaporated, washed, and dried to obtain a catalyst.

[0081] Comparative Preparation Example 2

[0082] Compared with Preparation Example 3, the difference is that step S2 is not performed.

[0083] The details are as follows:

[0084] S1. Preparation of wrinkled graphene oxide sheets: 1 mg / mL of graphene oxide aqueous dispersion was spray dried and ball milled for 1.5 h to obtain wrinkled graphene oxide sheets;

[0085] The spray drying conditions are as follows: the air inlet temperature is 90°C, the air outlet temperature is 40°C, and the evaporated water volume is 2000mL / h;

[0086] S2. Preparation of magnetically modified wrinkled sheets: 12 g of the wrinkled graphene oxide sheet obtained in step S1 was added to 100 mL of water, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, 5 g of ammonia water was added dropwise under nitrogen protection, heated to 75 ° C, stirred for 4 h, separated by magnet, washed, and dried to obtain a magnetically modified wrinkled sheet;

[0087] S3 copper / cobalt deposition: 5.5g copper chloride, 1.5g cobalt chloride was dissolved in 100mL water, 11g of the magnetically modified corrugated sheet obtained in step S2 and 8g disodium EDTA were added, the solvent was evaporated, washed, dried, and ball milled for 1.5h to obtain Cu / Co deposited magnetically modified corrugated sheet;

[0088] S4. Lanthanum doping: 0.7 g of lanthanum chloride was dissolved in 100 mL of water, 50 g of the Cu / Co deposited magnetic modified wrinkled sheet obtained in step S3 was added, the solvent was evaporated, washed, and dried to obtain a catalyst.

[0089] Comparative Preparation Example 3

[0090] Compared with Preparation Example 3, the difference is that step S3 is not performed.

[0091] The details are as follows:

[0092] S1. Preparation of wrinkled graphene oxide sheets: 1 mg / mL of graphene oxide aqueous dispersion was spray dried and ball milled for 1.5 h to obtain wrinkled graphene oxide sheets;

[0093] The spray drying conditions are as follows: the air inlet temperature is 90°C, the air outlet temperature is 40°C, and the evaporated water volume is 2000mL / h;

[0094] S2. Preparation of tannic acid modified wrinkled sheet: 10 g of the wrinkled graphene oxide sheet obtained in step S1 was added to 150 mL of water, 1.5 g of tannic acid and 0.25 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain a tannic acid modified wrinkled sheet;

[0095] The catalyst is a Tris-HCl solution with a pH of 9.3;

[0096] S3 copper / cobalt deposition: 5.5g copper chloride, 1.5g cobalt chloride was dissolved in 100mL water, 11g tannic acid modified pleated sheet obtained in step S2 and 8g disodium EDTA were added, the solvent was evaporated, washed, dried, and ball milled for 1.5h to obtain Cu / Co deposited magnetic modified pleated sheet;

[0097] S4. Lanthanum doping: 0.7 g of lanthanum chloride was dissolved in 100 mL of water, 50 g of the Cu / Co deposited modified wrinkled sheet obtained in step S3 was added, the solvent was evaporated, washed, and dried to obtain a catalyst.

[0098] Comparative Preparation Example 4

[0099] Compared with Preparation Example 3, the difference is that copper chloride is not added in step S4.

[0100] The details are as follows:

[0101] S1. Preparation of wrinkled graphene oxide sheets: 1 mg / mL of graphene oxide aqueous dispersion was spray dried and ball milled for 1.5 h to obtain wrinkled graphene oxide sheets;

[0102] The spray drying conditions are as follows: the air inlet temperature is 90°C, the air outlet temperature is 40°C, and the evaporated water volume is 2000mL / h;

[0103] S2. Preparation of tannic acid modified wrinkled sheet: 10 g of the wrinkled graphene oxide sheet obtained in step S1 was added to 150 mL of water, 1.5 g of tannic acid and 0.25 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain a tannic acid modified wrinkled sheet;

[0104] The catalyst is a Tris-HCl solution with a pH of 9.3;

[0105] S3. Preparation of magnetically modified pleated sheet: 12 g of the tannic acid-modified pleated sheet obtained in step S2 was added to 100 mL of water, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, 5 g of ammonia was added dropwise under nitrogen protection, heated to 75 ° C, stirred for 4 h, separated by magnet, washed, and dried to obtain a magnetically modified pleated sheet;

[0106] S4 cobalt deposition: 7g of cobalt chloride was dissolved in 100mL of water, 11g of the magnetically modified wrinkled sheet obtained in step S3 and 8g of disodium EDTA were added, the solvent was evaporated, washed, dried, and ball milled for 1.5h to obtain a Co-deposited magnetically modified wrinkled sheet;

[0107] S5. Lanthanum doping: 0.7 g of lanthanum chloride was dissolved in 100 mL of water, 50 g of the Co-deposited magnetic modified wrinkled sheet obtained in step S4 was added, the solvent was evaporated, washed, and dried to obtain a catalyst.

[0108] Comparative Preparation Example 5

[0109] Compared with Preparation Example 3, the difference is that cobalt chloride is not added in step S4.

[0110] The details are as follows:

[0111] S1. Preparation of wrinkled graphene oxide sheets: 1 mg / mL of graphene oxide aqueous dispersion was spray dried and ball milled for 1.5 h to obtain wrinkled graphene oxide sheets;

[0112] The spray drying conditions are as follows: the air inlet temperature is 90°C, the air outlet temperature is 40°C, and the evaporated water volume is 2000mL / h;

[0113] S2. Preparation of tannic acid modified wrinkled sheet: 10 g of the wrinkled graphene oxide sheet obtained in step S1 was added to 150 mL of water, 1.5 g of tannic acid and 0.25 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain a tannic acid modified wrinkled sheet;

[0114] The catalyst is a Tris-HCl solution with a pH of 9.3;

[0115] S3. Preparation of magnetically modified pleated sheet: 12 g of the tannic acid-modified pleated sheet obtained in step S2 was added to 100 mL of water, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, 5 g of ammonia was added dropwise under nitrogen protection, heated to 75 ° C, stirred for 4 h, separated by magnet, washed, and dried to obtain a magnetically modified pleated sheet;

[0116] S4 copper deposition: 7g of copper chloride was dissolved in 100mL of water, 11g of the magnetically modified corrugated sheet obtained in step S3 and 8g of disodium EDTA were added, the solvent was evaporated, washed, dried, and ball-milled for 1.5h to obtain a Cu-deposited magnetically modified corrugated sheet;

[0117] S5. Lanthanum doping: 0.7 g of lanthanum chloride was dissolved in 100 mL of water, 50 g of the Cu-deposited magnetic modified wrinkled sheet obtained in step S4 was added, the solvent was evaporated, washed, and dried to obtain a catalyst.

[0118] Comparative Preparation Example 6

[0119] Compared with Preparation Example 3, the difference is that step S4 is not performed.

[0120] The details are as follows:

[0121] S1. Preparation of wrinkled graphene oxide sheets: 1 mg / mL of graphene oxide aqueous dispersion was spray dried and ball milled for 1.5 h to obtain wrinkled graphene oxide sheets;

[0122] The spray drying conditions are as follows: the air inlet temperature is 90°C, the air outlet temperature is 40°C, and the evaporated water volume is 2000mL / h;

[0123] S2. Preparation of tannic acid modified wrinkled sheet: 10 g of the wrinkled graphene oxide sheet obtained in step S1 was added to 150 mL of water, 1.5 g of tannic acid and 0.25 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain a tannic acid modified wrinkled sheet;

[0124] The catalyst is a Tris-HCl solution with a pH of 9.3;

[0125] S3. Preparation of magnetically modified pleated sheet: 12 g of the tannic acid-modified pleated sheet obtained in step S2 was added to 100 mL of water, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, 5 g of ammonia was added dropwise under nitrogen protection, heated to 75 ° C, stirred for 4 h, separated by magnet, washed, and dried to obtain a magnetically modified pleated sheet;

[0126] S4. Lanthanum doping: 0.7 g of lanthanum chloride was dissolved in 100 mL of water, 50 g of the magnetically modified corrugated sheet obtained in step S3 was added, the solvent was evaporated, washed, and dried to obtain a catalyst.

[0127] Comparative Preparation Example 7

[0128] Compared with Preparation Example 3, the difference is that step S5 is not performed.

[0129] The details are as follows:

[0130] S1. Preparation of wrinkled graphene oxide sheets: 1 mg / mL of graphene oxide aqueous dispersion was spray dried and ball milled for 1.5 h to obtain wrinkled graphene oxide sheets;

[0131] The spray drying conditions are as follows: the air inlet temperature is 90°C, the air outlet temperature is 40°C, and the evaporated water volume is 2000mL / h;

[0132] S2. Preparation of tannic acid modified wrinkled sheet: 10 g of the wrinkled graphene oxide sheet obtained in step S1 was added to 150 mL of water, 1.5 g of tannic acid and 0.25 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain a tannic acid modified wrinkled sheet;

[0133] The catalyst is a Tris-HCl solution with a pH of 9.3;

[0134] S3. Preparation of magnetically modified pleated sheet: 12 g of the tannic acid-modified pleated sheet obtained in step S2 was added to 100 mL of water, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, 5 g of ammonia was added dropwise under nitrogen protection, heated to 75 ° C, stirred for 4 h, separated by magnet, washed, and dried to obtain a magnetically modified pleated sheet;

[0135] S4. Copper / cobalt deposition: 5.5 g of copper chloride and 1.5 g of cobalt chloride were dissolved in 100 mL of water, 11 g of the magnetically modified corrugated sheet obtained in step S3 and 8 g of disodium EDTA were added, the solvent was evaporated, washed, dried, and ball-milled for 1.5 h to obtain a Cu / Co deposited magnetically modified corrugated sheet, which was the catalyst.

[0136] Test Example 1

[0137] The specific surface areas of the catalyst samples prepared in Preparation Examples 1-3 and Comparative Preparation Examples 1-7 were measured using an ASAP2460 fully automatic specific surface area analyzer produced by Micromeritics Instruments. The results are shown in Table 1.

[0138] Table 1

[0139] Group <![CDATA[Specific surface area (m 2 / g)]]> Preparation Example 1 98.2 Preparation Example 2 101.1 Preparation Example 3 103.5 Comparative Preparation Example 1 13.2 Comparative Preparation Example 2 88.3 Comparative Preparation Example 3 83.6 Comparative Preparation Example 4 90.4 Comparative Preparation Example 5 91.7 Comparative Preparation Example 6 87.5 Comparative Preparation Example 7 95.6

[0140] As can be seen from the above table, the catalysts prepared in Preparation Examples 1-3 of the present invention have a higher specific surface area

[0141] Example 1

[0142] This embodiment provides a method for preparing sulfentrazone, comprising the following steps:

[0143] Synthesis route:

[0144]

[0145] Add 200mL of chlorobenzene to a four-necked flask equipped with a stirrer, a condenser, a thermometer and a dropping funnel, add 0.1mol of the intermediate and the catalyst prepared in Preparation Example 1, the amount of the catalyst added is 0.5wt% of the total mass of the reactants; stir and heat to reflux, add 0.105mol of methylsulfonyl chloride dropwise, add dropwise for 0.5h, reflux for dehydrochlorination reaction for 3h, the reaction is completed, and the catalyst is recovered by magnet separation. Cool down to about 80°C, add 150mL of tap water, stir and heat up to 95°C; let stand for stratification, remove the upper water layer; add 150mL of tap water to wash the lower chlorobenzene layer repeatedly; stir and cool the lower chlorobenzene layer to 5°C, crystallize, filter, dry, and recrystallize with methanol to obtain sulfentrazone.

[0146] Example 2

[0147] This embodiment provides a method for preparing sulfentrazone, comprising the following steps:

[0148] Add 200mL of chlorobenzene to a four-necked flask equipped with a stirrer, a condenser, a thermometer and a dropping funnel, add 0.1mol of the intermediate and the catalyst prepared in Preparation Example 2, the amount of the catalyst added is 1wt% of the total mass of the reactants; stir and heat to reflux, add 0.11mol of methylsulfonyl chloride dropwise, add dropwise for 0.5h, then reflux for dehydrochlorination reaction for 3h, the reaction is completed, and the catalyst is recovered by magnet separation. Cool down to about 80°C, add 150mL of tap water, stir and heat up to 95°C; let stand for stratification, remove the upper water layer; add 150mL of tap water again to repeatedly wash the lower chlorobenzene layer; stir and cool the lower chlorobenzene layer to 5°C, crystallize, filter, dry, and recrystallize with methanol to obtain sulfentrazone.

[0149] Example 3

[0150] This embodiment provides a method for preparing sulfentrazone, comprising the following steps:

[0151] Add 200mL of chlorobenzene to a four-necked flask equipped with a stirrer, a condenser, a thermometer and a dropping funnel, add 0.1mol of the intermediate and the catalyst prepared in Preparation Example 3, the amount of the catalyst added is 0.7wt% of the total mass of the reactants; stir and heat to reflux, add 0.107mol of methylsulfonyl chloride dropwise, add dropwise for 0.5h, reflux for dehydrochlorination reaction for 3h, the reaction is completed, and the catalyst is recovered by magnet separation. Cool down to about 80°C, add 150mL of tap water, stir and heat up to 95°C; stand and separate, remove the upper water layer; add 150mL of tap water to wash the lower chlorobenzene layer repeatedly; stir and cool the lower chlorobenzene layer to 5°C, crystallize, filter, dry, and recrystallize with methanol to obtain sulfentrazone.

[0152] Comparative Example 1

[0153] Compared with Example 3, the catalyst prepared in Comparative Preparation Example 1 was used to catalyze the reaction.

[0154] Comparative Example 2

[0155] Compared with Example 3, the catalyst prepared in Comparative Preparation Example 2 was used to catalyze the reaction.

[0156] Comparative Example 3

[0157] Compared with Example 3, the catalyst prepared in Comparative Preparation Example 3 was used to catalyze the reaction.

[0158] Comparative Example 4

[0159] Compared with Example 3, the catalyst prepared in Comparative Preparation Example 4 was used to catalyze the reaction.

[0160] Comparative Example 5

[0161] Compared with Example 3, the catalyst prepared in Comparative Preparation Example 5 was used to catalyze the reaction.

[0162] Comparative Example 6

[0163] Compared with Example 3, the catalyst prepared in Comparative Preparation Example 6 was used to catalyze the reaction.

[0164] Comparative Example 7

[0165] Compared with Example 3, the catalyst prepared in Comparative Preparation Example 7 was used to catalyze the reaction.

[0166] Test Example 2

[0167] The reactions in Examples 1-3 of the present invention and Comparative Examples 1-7 were evaluated. The results are shown in Table 2.

[0168] Table 2

[0169]

[0170] It can be seen from the above table that the methods in Examples 1-3 of the present invention can obtain sulfentrazone products with high yield and high purity.

[0171] Test Example 3

[0172] After the catalyst in Example 3 was recovered, the catalytic reaction was repeated 5 times according to the reaction conditions of Example 3 (a total of 6 reactions were performed). The results of the raw material conversion rate of the intermediate and the yield of the obtained sulfentrazone product in each reaction are shown in Table 3.

[0173] Table 3

[0174] Number of reactions Conversion rate of raw materials (intermediates) (%) Yield of product sulfentrazone (%) 1st time 99.9 98.9 2nd 99.4 98.3 3rd 99.2 98.0 4th 99.0 97.5 5th 98.8 97.2 6th 98.5 96.9

[0175] It can be seen from the above table that the catalyst in Example 3 of the present invention still maintains a relatively high catalytic activity after multiple reactions.

[0176] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing sulfentrazone, characterized in that: The intermediate and methylsulfonyl chloride are heated to reflux and stirred for reaction under the action of a catalyst to obtain sulfentrazone; the catalyst is a composite material in which magnetic ferrosoferric oxide and Cu and Co elements are deposited on the surface of a wrinkled graphene oxide sheet after being modified with tannic acid and doped with La element: The structural formula of the intermediate is shown in Formula II:

2. The preparation method according to claim 1, characterized in that: The molar ratio of the intermediate to methanesulfonyl chloride is 1:1.05-1.

1.

3. The preparation method according to claim 1, characterized in that: The added amount of the catalyst is 0.5-1 wt% of the total mass of the reactants.

4. The preparation method according to claim 1, characterized in that: The preparation method of the catalyst is as follows: S1. Preparation of wrinkled graphene oxide sheets: spray drying a graphene oxide aqueous dispersion, and ball milling to obtain wrinkled graphene oxide sheets; S2. Preparation of tannic acid modified wrinkled sheet: adding the wrinkled graphene oxide sheet obtained in step S1 to water, adding tannic acid and a catalyst, heating and stirring to react, centrifuging, washing, and drying to obtain a tannic acid modified wrinkled sheet; S3. Preparation of magnetically modified corrugated sheet: adding the tannic acid modified corrugated sheet obtained in step S2 to water, adding ferric chloride and ferrous chloride, adding ammonia water dropwise under inert gas protection, heating and stirring the reaction, separating with a magnet, washing, and drying to obtain a magnetically modified corrugated sheet; S4. Copper / cobalt deposition: dissolving a copper salt and a cobalt salt in water, adding the magnetically modified corrugated sheet and the complexing agent obtained in step S3, evaporating the solvent, washing, drying, and ball milling to obtain a Cu / Co deposited magnetically modified corrugated sheet; S5. Lanthanum doping: dissolve lanthanum salt in water, add the Cu / Co deposited magnetic modified wrinkled sheet obtained in step S4, evaporate the solvent, wash, dry, and obtain a catalyst.

5. The preparation method according to claim 4, characterized in that: The concentration of the graphene oxide aqueous dispersion in step S1 is 0.5-1 mg / mL, the spray drying conditions are: an inlet air temperature of 80-100° C., an outlet air temperature of 30-50° C., an evaporated water volume of 1700-2200 mL / h, and the ball milling time is 1-2 h.

6. The preparation method according to claim 4, characterized in that: The mass ratio of the wrinkled graphene oxide sheet, tannic acid and catalyst in step S2 is 10:1-2:0.2-0.3, the catalyst is a Tris-HCl solution with a pH of 9-9.5, the temperature of the heating and stirring reaction is 40-50° C., and the time is 2-4 hours.

7. The preparation method according to claim 4, characterized in that: The mass ratio of the tannic acid modified pleated sheet, ferric chloride, ferrous chloride and ammonia water in step S3 is 10-15: 3.2-3.3:1.2-1.3:4-6, the temperature of the heating and stirring reaction is 70-80°C, and the time is 3-5h.

8. The preparation method according to claim 4, characterized in that: In step S4, the copper salt is selected from at least one of copper chloride, copper acetate, copper sulfate, and copper nitrate, the cobalt salt is cobalt chloride, the complexing agent is at least one of EDTA, disodium EDTA, ethylenediamine, and triethylamine, the mass ratio of the copper salt, the cobalt salt, the magnetically modified corrugated sheet, and the complexing agent is 5-6:1-2:10-12:7-10, and the ball milling time is 1-2h.

9. The preparation method according to claim 4, characterized in that: The lanthanum salt in step S5 is lanthanum chloride, and the mass ratio of the lanthanum salt to the Cu / Co deposited magnetic modified corrugated sheet is 0.5-1:

50.

10. A catalyst, characterized in that The preparation method comprises the following steps: S1. Preparation of wrinkled graphene oxide sheets: spray-drying a 0.5-1 mg / mL aqueous dispersion of graphene oxide, and ball-milling for 1-2 h to obtain wrinkled graphene oxide sheets; The spray drying conditions are as follows: the air inlet temperature is 80-100°C, the air outlet temperature is 30-50°C, and the evaporated water volume is 1700-2200mL / h; S2. Preparation of tannic acid modified wrinkled sheet: 10 parts by weight of the wrinkled graphene oxide sheet obtained in step S1 is added to water, 1-2 parts by weight of tannic acid and 0.2-0.3 parts by weight of catalyst are added, heated to 40-50°C, stirred for reaction for 2-4h, centrifuged, washed, and dried to obtain a tannic acid modified wrinkled sheet; The catalyst is a Tris-HCl solution with a pH of 9-9.5; S3. Preparation of magnetically modified corrugated sheet: 10-15 parts by weight of the tannic acid modified corrugated sheet obtained in step S2 is added to water, 3.2-3.3 parts by weight of ferric chloride and 1.2-1.3 parts by weight of ferrous chloride are added, 4-6 parts by weight of ammonia water are added dropwise under inert gas protection, heated to 70-80 ° C, stirred for 3-5h, separated by magnet, washed, and dried to obtain a magnetically modified corrugated sheet; S4 copper / cobalt deposition: 5-6 parts by weight of copper salt, 1-2 parts by weight of cobalt salt dissolved in water, adding 10-12 parts by weight of the magnetically modified corrugated sheet obtained in step S3 and 7-10 parts by weight of a complexing agent, evaporating the solvent, washing, drying, ball milling 1-2h, to obtain a Cu / Co deposited magnetically modified corrugated sheet; S5. Lanthanum doping: Dissolve 0.5-1 parts by weight of lanthanum chloride in water, add 50 parts by weight of the Cu / Co deposited magnetic modified wrinkled sheet obtained in step S4, evaporate the solvent, wash, and dry to obtain a catalyst.